Hippocampal subfield volume differences between female-to-male transgender individuals with cross-sex hormone therapy and cisgender women - Kim, Gwang-Won; Lee, Mina; Lee, Hyun-Suk; Park, Kwangsung; Jeong, Gwang-Woo (Frontiers in Neuroscience, 2025)
IntroductionThe prevalence of female-to-male (FtM) transgender individuals has risen recently, yet the effects of cross-sex hormone therapy on volumetric differences in the hippocampal subfields remain poorly understood. This study aimed to evaluate the differences of gray matter (GM) volume, especially focusing on the hippocampal subfields, in FtM transgender individuals and premenopausal cisgender women.MethodsSeventeen FtM transgender individuals who had undergone hysterectomies and were receiving testosterone therapy before participating in this study, along with 20 premenopausal women, underwent a single session of T1-weighted magnetic resonance imaging (MRI).ResultsFtM transgender group had significantly higher free-testosterone (free-T) levels and lower estradiol levels compared with premenopausal women group (p < 0.001). In voxel-wise analysis, FtM transgender individuals showed significantly larger GM volumes in the caudate nucleus, hypothalamus, and thalamus compared with premenopausal women (p < 0.01, FWE-corrected). More specifically, the right hippocampal subiculum volume was larger in FtM transgender individuals (p < 0.05, Bonferroni-corrected), and these volumes were positively correlated with the free-T levels (r = 0.34, p = 0.04). This study revealed the specific hippocampal subfield volume differences in the testosterone-treated FtM transgender group when compared to cisgender premenopausal women group.DiscussionThese findings might help elucidate the morphological variation of the specific cerebral regions associated with testosterone therapy in FtM transgender individuals and contribute to our understanding of the effects of gender-affirming hormone treatments as well.